POST-TONSILLECTOMY AND ADENOTONSILLECTOMY MORBIDITY & COMPLICATIONS AT DISTRICT HEADQUARTER HOSPITAL DAGGAR - ULLAH, ZAKIR (Journal of Ayub Medical College Abbottabad, 2001)
Background: Tonsillectomy or adenotonsillectomy is one of the commonly performed operation in ENT practice. Morbidity & complications associated with tonsillectomy and adenotonsillectomy include severe otalgia, pyrexia, odynophagia and haemorrhage Methods: A prospective study was undertaken from April 1996 to April 2001 to report the experience regarding postoperative morbidity' complications in tonsillectomy and or adenotonsillectomy. A total of 1500 patients undergoing tonsillectomy or adenotonsillectomy, for chronic-recurrent tonsillitis or adenotonsillar hypertrophy were included. These patients received antibiotic in the form of amoxycillin and clavulanic acid and non-salicylate analgesics for 7 days postoperatively. 100 patients were lost to follow up Results: Seventy' percent of patients were female and thirty percent males with maximum number of patients between the age of 11-22 years. Postoperative complications developed in 25 out of 1400 patients. 14 of them developed post-operative bleeding and 9 developed postoperative infection. Conclusions: It was found that postoperative morbidity complications were less in this study with regard to secondary haemorrhage, operative site infection, intensity &. duration of postoperative pain, postoperative pyrexia and time for return to normal activities.